Coating composition containing melamine cyanurate particles

The coating composition with melamine cyanurate and a polymer polysaccharide dispersant addresses the sedimentation and stability issues in existing lubricating compositions, achieving enhanced dispersion stability and spray coating performance.

JP7648981B2Active Publication Date: 2025-03-19NISSAN CHEM CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021058010
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-30
Publication Date
2025-03-19
Estimated Expiration
2041-03-30

AI Technical Summary

Technical Problem

Existing lubricating compositions containing melamine cyanurate face challenges with precipitability, redispersion difficulties, and inadequate water dispersion stability, leading to sedimentation issues and poor coating properties when applied by spray coating.

Method used

A coating composition incorporating melamine cyanurate particles and a specific polymer polysaccharide as a dispersant, which suppresses the sedimentation of melamine cyanurate particles and enhances the coating's storage stability and spray coating performance.

Benefits of technology

The composition achieves excellent dispersion stability of melamine cyanurate, preventing sedimentation over a long period and ensuring a uniform coating surface without liquid droplets, thereby improving the coating's overall performance and usability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007648981000001
    Figure 0007648981000001
  • Figure 0007648981000002
    Figure 0007648981000002
  • Figure 0007648981000003
    Figure 0007648981000003
Patent Text Reader

Abstract

To provide a composition for coating which is excellent in dispersion stability of melamine cyanurate, and can suppress precipitation of melamine cyanurate over a long period of time in an aqueous coating agent containing melamine cyanurate for imparting a lubricant film to a mold or the like, and a composition for coating which enables spray coating such as spray and hardly causes liquid sagging on a coated surface after spray coating.SOLUTION: There are provided a composition for coating that contains melamine cyanurate particles, polymer polysaccharides, and water, and contains more than 0.05 mass% and less than 1.0 mass% of the polymer polysaccharides with respect to the total mass of the composition for coating; and a method for spray coating the composition for coating, and forming a film.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a water-based coating composition containing melamine cyanurate particles. [Background technology]

[0002] Triazine derivatives are used in various industrial fields as flame retardants, antioxidants, rust inhibitors, industrial preservatives, and lubricants. Among triazine derivatives, melamine cyanurate is used as an organic solid lubricant in lubricating oils and greases, and is also used together with binders in paints and lubricating coatings for sliding parts. For example, there has been proposed a lubricant composition that contains, in addition to melamine cyanurate, a lubricant oil, a wax, an anionic surfactant, and an aqueous solvent, so that melamine cyanurate can be applied to a substrate (Patent Document 1). In addition, in a water-based lubricant film treatment agent for a solid formed by blending a branched carboxylic acid and a solid film component, melamine cyanurate is exemplified as a supplementary component that assists lubrication under high processing loads and exhibits extreme pressure effects (Patent Document 2). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2008-088297 A [Patent Document 2] JP 2006-335838 A Summary of the Invention [Problem to be solved by the invention]

[0004] The lubricating composition described in Patent Document 1 has poor handleability because the melamine cyanurate has a tendency to settle and must be redispersed when used. In addition, in Patent Document 2, the aggregation property of dispersed fine particles is evaluated in an accelerated test (80°C / 120 hours treatment) as the liquid stability, but the settling property of dispersed fine particles is not evaluated. In addition, there is no example in which melamine cyanurate, which is exemplified as a supplementary component, is blended with a water-based lubricant coating agent, and the water dispersion stability of melamine cyanurate by the technology of this document cannot be confirmed.

[0005] The present invention aims to provide a coating composition which, in an aqueous coating agent containing melamine cyanurate for providing a lubricating coating film to a mold or the like, has excellent dispersion stability of melamine cyanurate and can suppress sedimentation of melamine cyanurate over a long period of time, and further which can be applied by spray application, etc., and which is unlikely to cause dripping on the coated surface after spray application. [Means for solving the problem]

[0006] Means for Solving the Problems The present inventors have conducted intensive research to solve the above problems, and as a result have found that by employing a specific polymeric polysaccharide as a dispersant in a coating composition containing melamine cyanurate particles and water, settling of the melamine cyanurate particles in the composition is suppressed, resulting in a composition with excellent storage stability; and further, that the composition can be applied by spraying, a uniform coating surface can be obtained without dripping, and the composition has excellent coatability on a coating target such as a mold, and have thus completed the present invention.

[0007] That is, in a first aspect, the present invention relates to a coating composition comprising melamine cyanurate particles, a polymeric polysaccharide, and water, the polymeric polysaccharide being contained in an amount of more than 0.05 mass% and less than 1.0 mass% relative to the total mass of the coating composition. As a second aspect, the present invention relates to the coating composition according to the first aspect, in which the melamine cyanurate particles have an average particle size of 0.1 to 100 μm. As a third aspect, the present invention relates to the coating composition according to the first or second aspect, in which the polymeric polysaccharide is a polysaccharide having a carboxylate anion in water. As a fourth aspect, the present invention relates to the coating composition according to the first or second aspect, in which the polymeric polysaccharide is a water-insoluble polysaccharide selected from the group consisting of cellulose, chitin, chitosan, and carboxylic acid-modified products thereof. As a fifth aspect, the present invention relates to the coating composition according to the first or second aspect, in which the polymeric polysaccharide is a water-soluble polysaccharide selected from the group consisting of hyaluronic acid, gellan gum, deacylated gellan gum, rhamsan gum, diutan gum, xanthan gum, carrageenan, salts thereof, and carboxylic acid-modified products thereof. As a sixth aspect, the present invention relates to the coating composition according to any one of the first to fifth aspects, in which the polymeric polysaccharide is contained in an amount of 0.1 to 0.5 mass % relative to the total mass of the coating composition. As a seventh aspect, the present invention relates to the coating composition according to any one of the first to sixth aspects, in which the melamine cyanurate particles are contained in an amount of 0.1 to 20 mass % relative to the total mass of the coating composition. As an eighth aspect, the present invention relates to a method for forming a coating film containing melamine cyanurate particles by spraying the coating composition according to any one of the first to seventh aspects onto a substrate. Effect of the Invention

[0008] According to the present invention, there can be provided a coating composition for forming a lubricating coating, which inhibits sedimentation of melamine cyanurate particles in water as a dispersion medium, does not drip even after application to a substrate by spraying, and has excellent storage stability and application properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] As mentioned in the above-mentioned Patent Document 1, a technique for forming a lubricating coating containing melamine cyanurate by coating has been proposed, but it is not easy to suppress the sedimentation of melamine cyanurate particles in an aqueous medium for a long period of time. In the technical field of particle dispersion, it is known that particles and dispersion media have compatibility, and a dispersion medium that is excellent for dispersing one type of particle cannot be immediately used as a dispersion medium for another type of particle. Dispersibility can change significantly depending on the chemical and physical properties, such as the type and size of the particle, and the type and viscosity of the dispersion medium. Even if the same type of particle and dispersion medium are selected, it is difficult to predict their dispersibility if there is a slight change in the properties or characteristics.

[0010] While proceeding with the design of an aqueous coating composition containing melamine cyanurate particles, the present inventors investigated various dispersants, such as conventional low molecular weight dispersants such as surfactants and polymer-type polymer dispersants, which satisfy the required performance of suppressing sedimentation of the particles for a long period of time, for example, 10 hours. In particular, the present inventors have been studying dispersants that can suppress sedimentation for a long period of time, even for particles of a relatively large particle size of the order of microns. For micron-sized particles, it is difficult to suppress sedimentation by applying a surfactant-type low-molecular dispersant or a conventional polymer dispersant such as a water-soluble polymer. In addition, although a technology has been proposed for culturing cells or tissues by suspending (dispersing) them in a structure that forms a three-dimensional network in water (for example, International Publication No. 2014 / 017513), it has not been confirmed so far whether micron-sized particles can be dispersed in such a structure. Furthermore, the present inventors have considered the usability of the above coating composition and have been studying a coating composition that can achieve good coating properties on a target object, particularly when sprayed, without causing dripping, etc. The occurrence / prevention of dripping is related to the thixotropy rather than the viscosity of the composition. Even if a spray composition that satisfies the viscosity range in which dripping is suppressed is designed, it is difficult to sufficiently It is unclear whether thixotropy will be exhibited, and in systems that do not exhibit thixotropy, there is a risk of dripping.

[0011] The present inventors have conducted various investigations into the compatibility between particles and dispersion media, the expression of thixotropy, and the like, and have found that by using a polymeric polysaccharide, in particular a polymeric polysaccharide containing a carboxy group or a salt of a carboxy group, as a dispersant in an aqueous dispersion of melamine cyanurate, it is possible to suppress the settling of micron-order melamine cyanurate particles and also to suppress dripping during spray application. The present invention will be described in detail below.

[0012] [Melamine cyanurate particles] Melamine cyanurate is an addition compound of melamine and cyanuric acid or isocyanuric acid, and has a structure in which melamine molecules with a six-membered ring structure and cyanuric acid (isocyanuric acid) molecules are bonded by hydrogen bonds and arranged in a plane.The planar structure overlaps in layers to form a multilayer structure (mica-like), which has cleavage properties and is thought to contribute to solid lubrication. The melamine cyanurate particles used in the present invention may have an average particle size of, for example, 0.1 to 100 μm. The average particle size of the melamine cyanurate particles used in the present invention may be preferably 0.2 to 20 μm, more preferably 1 to 14 μm. Here, the average particle size can be measured by a laser diffraction scattering method. As the melamine cyanurate particles, commercially available products can be used, such as MC-4000, MC-4500, and MC-6000 manufactured by Nissan Chemical Industries, Ltd.

[0013] In general, when particles are dispersed in an aqueous dispersion medium or the like, it is desirable to use extremely fine particles having a particle size of, for example, 1 μm or less, on the order of nanometers, in order to prevent the particles from settling, and melamine cyanurate particles are no exception. In the present invention, even if the melamine cyanurate particles have an average particle size of microns, which is relatively large compared to such nanometer-order particles, the settling of the particles can be suppressed for a long period of time.

[0014] In the coating composition of the present invention, the amount of melamine cyanute particles to be blended can be appropriately determined taking into consideration various factors such as the type and amount of the polymeric polysaccharide described below, the purpose of use of the composition, and the method of application of the composition (spray coating). For example, it can be blended in an amount of 0.1 to 20% by mass relative to the total mass of the composition.

[0015] [High molecular weight polysaccharide] The coating composition of the present invention contains a polymeric polysaccharide. The polymeric polysaccharide can have the function of preventing the melamine cyanurate particles from settling and improving the coating property. The polymeric polysaccharide is present in the composition in a state of being dissolved or dispersed in water.

[0016] The polymeric polysaccharide may be a water-insoluble polysaccharide selected from the group consisting of cellulose, chitin, and chitosan; or a water-soluble polysaccharide selected from the group consisting of hyaluronic acid, gellan gum, deacylated gellan gum, rhamsan gum, diutan gum, xanthan gum, carrageenan, and salts thereof. Furthermore, carboxylic acid-modified products of these water-insoluble or water-soluble polysaccharides may be used. These may be used alone or in combination of two or more. These polymeric polysaccharides preferably have a fibrous shape.

[0017] Among these polymeric polysaccharides, polysaccharides having carboxylate anions in the polymer chain in water can be preferably used. In other words, polysaccharides have a carboxyl group (-COOH) or a carboxyl salt structure (-COOM) and form carboxylate ions (-COO - ) refers to those that form For example, among the specific compounds listed above as the water-insoluble and water-soluble polysaccharides, polysaccharides having a carboxylate anion in water (polysaccharides having a carboxy group and / or a salt structure of a carboxy group) and, when the above compounds are polysaccharides not having a carboxylate anion in water (polysaccharides not containing a carboxy group, etc.), carboxylic acid modified products of the polysaccharides (polysaccharides into which a carboxy group and / or a salt structure of a carboxy group has been introduced) can be preferably used. Examples of the salt of the carboxy group include salts of alkali metals such as Na and K, and salts of alkaline earth metals such as Ca and Mg. The polymeric polysaccharide has a carboxyl group and / or a salt structure of a carboxyl group in its polymer chain, i.e., a carboxylate ion (-COO - ), it is presumed that the repulsion between these ions and interactions such as van der Waals forces facilitate the formation of a three-dimensional structure in the medium, and that, for example, the melamine cyanurate particles are captured in the structure, thereby enhancing the effect of inhibiting the sedimentation of the melamine cyanurate particles.

[0018] As the above-mentioned polysaccharides, particularly polysaccharides having a carboxy group and / or a salt structure of a carboxy group that forms a carboxylate ion in water, cellulose having a carboxy group and deacylated gellan gum can be preferably used. The above-mentioned deacylated gellan gum forms a strong gel in the presence of cations, and is known to ionically crosslink carboxyl groups to form a gel (three-dimensional meshwork), particularly in the presence of multivalent cations such as Ca ions.

[0019] As these polysaccharides, for example polysaccharides having a carboxyl group and / or a salt structure of a carboxyl group, commercially available products can be used. An example of the cellulose having a carboxy group, which is an example of the polymeric polysaccharide having a carboxy group, is the product name "LEOCRYSTA (registered trademark)" series (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.). Furthermore, an example of deacylated gellan gum, which is an example of a polymeric polysaccharide having a carboxy group, is available under the trade name "KELCOGEL (registered trademark) CG-LA" (Sansho Corporation).

[0020] In the coating composition of the present invention, the amount of the polymeric polysaccharide may be more than 0.05% by mass and less than 1.0% by mass, preferably 0.1 to 0.5% by mass, based on the total mass of the composition. By setting the amount within the above range, the settling of the melamine cyanurate particles in a medium mainly composed of water can be suppressed, and dripping is less likely to occur on the sprayed surface when sprayed.

[0021] The coating composition of the present invention contains the above-mentioned melamine cyanurate particles, the above-mentioned polymeric polysaccharide, and water. The water content in the coating composition is 79.5% by mass to 99.8% by mass.

[0022] [Other ingredients] The coating composition of the present invention may contain other components in addition to those described above, provided that the effects of the present invention are not impaired. Examples of other components include solid lubricants other than melamine cyanurate particles, surfactants, water-soluble organic solvents, and the like.

[0023] Examples of the solid lubricant include graphite, molybdenum disulfide, boron nitride, polytetrafluoroethylene (PTFE), zinc stearate, and the like.

[0024] The surfactant is used for the purpose of improving the dispersibility of the melamine cyanurate particles and other solid lubricants and suppressing sedimentation. For example, the surfactants listed below in (1) to (4) can be used. (1) Anionic surfactants (1-1) Carboxylic acid type: aliphatic monocarboxylates, polyoxyethylene alkyl ether carboxylates, N-acylsarcosine salts, N-acylglutamates, and the like. (1-2) Sulfonic acid type: linear alkylbenzenesulfonate, alkyl (branched) benzenesulfonate, naphthalenesulfonate-formaldehyde condensate, alkylnaphthalenesulfonate, N-methyl-N-aryltaurine salt, etc. (1-3) Sulfate ester type: alkyl sulfates, polyoxyethylene alkyl ether sulfates, fat and oil sulfates, etc. (1-4) Phosphate ester type: polyoxyethylene alkyl ether phosphate, polyoxyethylene alkyl phenyl ether phosphate, etc. (2) Nonionic surfactants (2-1) Ester type: glycerin fatty acid esters, sorbitan fatty acid esters, sucrose fatty acid esters, etc. (2-2) Ether type: polyoxyethylene alkyl phenyl ether, polyoxyethylene polyoxypropylene glycol, etc. (2-3) Ester ether type: fatty acid polyethylene glycol, fatty acid polyoxyethylene sorbitan, etc. (2-4) Alkanolamide type: fatty acid alkanolamides, etc. (3) Cationic surfactants (3-1) Alkylamine type: monoalkylamine salts, dialkylamine salts, trialkylamine salts, etc. (3-2) Quaternary ammonium salt type: alkyltrimethylammonium halide (chloride, bromide, or iodide), dialkyldimethylammonium halide (chloride, bromide, or iodide), alkylbenzalkonium chloride, etc. (4) Amphoteric surfactants (4-1) Carboxybetaine type: alkylbetaine, fatty acid amidopropylbetaine, etc. (4-2) Derivatives of 2-alkylimidazolines: 2-alkyl-N-carboxymethyl-N-hydroxyethylimidazolium betaines, etc. (4-3) Glycine type: alkyl (or dialkyl) diethylenetriaminoacetic acid, etc. (4-4) Amine oxide type: alkylamine oxide, etc.

[0025] Examples of the water-soluble organic solvent include alcohols (for example, methanol, ethanol, propanol, butanol, isopropanol, and isobutanol) and glycols (for example, ethylene glycol, diethylene glycol, cellosolve, methyl cellosolve, and butyl cellosolve).

[0026] The coating composition of the present invention can be applied to an object to be coated using a brush, by spraying, or by immersion coating in the coating composition. The present invention also relates to a method for forming a coating film containing melamine cyanurate particles by spraying the coating composition onto a substrate. EXAMPLES

[0027] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the following examples.

[0028] Coating compositions of Examples and Comparative Examples were prepared in the amounts shown in Tables 1 to 4 below. The details of each component used in preparing the coating composition are as follows.

[0029] (1) Melamine cyanurate (MC) particles: (1-1) MC-6000 (Nissan Chemical Co., Ltd., average particle size <2 μm) (1-2) MC-4500 (Nissan Chemical Co., Ltd., average particle size <10 μm)

[0030] (2) Dispersant (2-1) Carboxy group-containing polymeric polysaccharides A 2.0% by mass aqueous dispersion of cellulose nanofibers to which a carboxy group had been introduced (LEOCRYSTA (registered trademark) I-2SX, manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.) was used as an aqueous dispersion of a dispersant (2-1). (2-2) Carboxylic acid-containing polysaccharides A polymer FP001 (manufactured by Nissan Chemical Industries, Ltd.) mainly composed of gellan gum was used as a salt-containing polymeric polysaccharide of a carboxy group. In detail, a 0.8% by mass aqueous solution of deacylated gellan gum (KELCOGEL (registered trademark) CG-LA, Sansho Corporation) was prepared, and this was heat-treated in an autoclave at 121°C for 20 minutes. Next, 40 g of the heat-treated deacylated gellan gum (FP001) was heated and stirred at 70°C, and 88 g of a 7 mM calcium chloride aqueous solution was slowly added dropwise and mixed therein so that the concentration of the deacylated gellan gum became 0.25% by mass, to prepare an aqueous solution of dispersant (2-2). (2-3) Non-carboxyl group-containing polymeric compounds A 2.0% by mass aqueous solution of polyvinyl alcohol (Mowiol (registered trademark) 10-98, weight average molecular weight: 61,000, Sigma-Aldrich Corporation) was prepared (dissolved by heating at 90° C.) to prepare an aqueous solution of dispersant (2-3). (2-4) Low molecular weight compounds A solution containing 25% by mass of sodium polyoxyethylene lauryl ether acetate (average repeating unit of polyoxyethylene: 4.5) (also known as sodium POE lauryl ether acetate, 4.5EO), a surfactant containing a carboxy group, represented by the following formula [1] was used as the dispersant (2-4) aqueous solution. [ka]

[0031] Example 1 0.75 g of melamine cyanurate particles (1-1) was weighed into a container, 7.5 g of the aqueous dispersion of dispersant (2-1) was added, and pure water was added to make a total of 30 g. The mixture was stirred at room temperature for 2 hours to obtain a coating composition of Example 1 containing carboxyl group-containing cellulose nanofibers. (Examples 2 to 15, Comparative Examples 1 to 3) Coating compositions of Examples 2 to 15 and Comparative Examples 1 to 3 were obtained in the same manner as in Example 1, except that the blending amounts of the dispersant (2-1) aqueous dispersion and the melamine cyanurate particles (1-1) were changed. Table 1 shows the concentrations of the dispersant (2-1: cellulose nanofibers) and melamine cyanurate particles (MC(1-1)) in each of the coating compositions of Examples 1 to 15 and Comparative Examples 1 to 3.

[0032] (Example 16) 0.75 g of melamine cyanurate particles (1-2) was weighed into a container, 7.5 g of the aqueous dispersion of dispersant (2-1) was added, and pure water was added to make a total of 30 g. The mixture was stirred at room temperature for 2 hours to obtain a coating composition of Example 16 containing carboxyl group-containing cellulose nanofibers. (Examples 17 to 29, Comparative Examples 4 to 6) Coating compositions of Examples 17 to 29 and Comparative Examples 4 to 6 were obtained in the same manner as in Example 16, except that the amounts of the dispersant (2-1) aqueous dispersion and the melamine cyanurate particles (1-2) were changed. Table 2 shows the concentrations of the dispersant (2-1: cellulose nanofibers) and melamine cyanurate particles (MC(1-2)) in each of the coating compositions of Examples 16 to 29 and Comparative Examples 4 to 6.

[0033] (Example 30) 0.75 g of melamine cyanurate particles (1-1) was weighed into a container, 28.8 g of the aqueous solution of dispersant (2-2) was added, and pure water was added to make a total of 30 g. The mixture was stirred at room temperature for 2 hours to obtain a melamine cyanurate coating composition of Example 30 containing deacylated gellan gum. (Examples 31 to 38, Comparative Examples 7 to 9) Coating compositions of Examples 31 to 38 and Comparative Examples 7 to 9 were obtained in the same manner as in Example 30, except that the amounts of the dispersant (2-2) aqueous solution and the melamine cyanurate particles (1-1) were changed. Table 3 shows the concentrations of the dispersant (2-2: deacylated gellan gum) and melamine cyanurate particles (MC(1-1)) in each of the coating compositions of Examples 30 to 38 and Comparative Examples 7 to 9.

[0034] Comparative Example 10 0.75 g of melamine cyanurate particles (1-1) was weighed into a container, 7.5 g of the aqueous solution of dispersant (2-3) was added, and further pure water was added to make a total of 30 g. The mixture was stirred at room temperature for 2 hours to obtain a coating composition of Comparative Example 10 containing polyvinyl alcohol. (Comparative Examples 11 to 24) Coating compositions of Comparative Examples 11 to 24 were obtained in the same manner as in Comparative Example 10, except that the amounts of the dispersant (2-3) aqueous solution and the melamine cyanurate particles (1-1) were changed. Table 4 shows the concentrations of the dispersant (2-3: polyvinyl alcohol) and the melamine cyanurate particles (MC(1-1)) in each of the coating compositions of Comparative Examples 10 to 24.

[0035] Comparative Example 25 0.75 g of melamine cyanurate particles (1-1) was weighed into a container, 7.5 g of the aqueous solution of dispersant (2-4) was added, and further pure water was added to make a total of 30 g. The mixture was stirred at room temperature for 2 hours to obtain a coating composition of Comparative Example 25 containing sodium polyoxyethylene lauryl ether acetate. (Comparative Examples 26 to 31) Coating compositions of Comparative Examples 26 to 31 were obtained in the same manner as in Comparative Example 25, except that the amounts of the dispersant (2-4) aqueous solution and the melamine cyanurate particles (1-1) were changed. Table 5 shows the concentrations of the dispersant (2-4: sodium polyoxyethylene lauryl ether acetate) and the melamine cyanurate particles (MC(1-1)) in each of the coating compositions of Comparative Examples 25 to 31.

[0036] (Comparative Example 32) 0.75 g of melamine cyanurate particles (1-2) was weighed into a container, 7.5 g of the aqueous solution of dispersant (2-4) was added, and pure water was added to make a total of 30 g. The mixture was stirred at room temperature for 2 hours to obtain a coating composition of Comparative Example 32 containing sodium polyoxyethylene lauryl ether acetate. (Comparative Examples 33 to 38) Coating compositions of Comparative Examples 33 to 38 were obtained in the same manner as in Comparative Example 32, except that the amounts of the dispersant (2-4) aqueous solution and the melamine cyanurate particles (1-2) were changed. Table 6 shows the dispersant (2-4: sodium polyoxyethylene lauryl ether acetate) and melamine cyanurate particles (MC(1-2)) in each coating composition of Comparative Examples 32 to 38. The concentrations of each are shown.

[0037] [1] Sedimentation prevention evaluation The settling properties of the melamine cyanurate particles in the coating compositions of the Examples and Comparative Examples were evaluated by the following method. A 15 mL centrifuge tube (MS-56150, made of PP) manufactured by Sumitomo Bakelite Co., Ltd. was filled with each of the coating compositions of the above-mentioned Examples and Comparative Examples up to the 14 mL mark on the centrifuge tube. The degree of sedimentation of the melamine cyanurate particles in the centrifuge tube was visually confirmed at the predetermined elapsed times (0 hours to 168 hours) shown in Tables 1 to 6. When separation into a transparent portion and a cloudy portion (particle-containing portion) was observed in the composition in the centrifuge tube, it was determined that sedimentation of the melamine cyanurate particles had occurred, and the sedimentation retention rate (%) [= (melamine cyanurate particle sedimentation scale / composition top scale) × 100] was calculated from the top liquid level of the coating composition in the centrifuge tube (composition top scale) and the top scale of the cloudy portion (melamine cyanurate particle sedimentation scale). If the sedimentation retention rate is 99% or more after 24 hours and 94% or more after 168 hours, it can be evaluated as suitable. The results are shown in Tables 1 to 6.

[0038] [2] Evaluation of dripping during spray application The dripping properties of the coating compositions of the Examples and Comparative Examples during spray coating were evaluated by the following method. A TRUSCO cap bottle with finger spray TFSB-20 (TRUSCO Nakayama Corporation, capacity 20 mL) was filled with 10 to 15 mL of each coating composition of the Examples and Comparative Examples. A glass substrate (limestone glass, washed with pure water and isopropanol and then dried) was set upright, and the coating composition filled in the cap bottle was sprayed onto the surface of the glass substrate (discharged perpendicular to the glass substrate, one push from a position 8 cm from the glass substrate). The presence or absence of dripping of the sprayed coating on the surface of the glass substrate was visually confirmed, and evaluated according to the following evaluation criteria. The obtained results are shown in Tables 1 to 6. <Evaluation criteria for dripping resistance> ○: No dripping or very little dripping ×: Dripping of the sprayed coating material was observed at the same time as it was attached to the glass substrate.

[0039] [Table 1]

[0040] As shown in Table 1, the coating composition of the example using carboxyl group-containing cellulose nanofiber [dispersant (2-1)], which is a polymeric polysaccharide, had a 9% water content even after 168 hours. It showed a sedimentation retention rate of 4% or more, and in an evaluation of dripping during spray application, almost no dripping occurred, confirming that it was possible to achieve both a high sedimentation retention rate and good dripping suppression effects. On the other hand, in the comparative coating composition in which the blending amount of dispersant (2-1) was 0.05 mass % or less, the sedimentation retention rate after 24 hours was 96% or less, and after 168 hours it was below 90%. Thus, satisfactory results could not be obtained in both the inhibition of sedimentation and the inhibition of dripping during spray coating.

[0041] [Table 2]

[0042] Furthermore, as shown in Table 2, even when using melamine cyanurate particles MC-4500 (average particle size <10 μm) with a large particle size, the coating composition of the embodiment using carboxyl-containing cellulose nanofibers [dispersant (2-1)], which is a polymeric polysaccharide, showed a high sedimentation retention rate of 97% or more after 168 hours. In addition, in the evaluation of dripping during spray coating, almost no dripping occurred, confirming that it is possible to achieve both a high sedimentation retention rate and a good dripping suppression effect. On the other hand, in the coating composition of the comparative example in which the blending amount of dispersant (2-1) was 0.05 mass% or less, the sedimentation retention rate after 24 hours was maintained at a relatively high value (97% or more), but when the blending amount of melamine cyanurate particles was increased, the sedimentation retention rate significantly decreased after 168 hours. In addition, dripping was confirmed in both cases, and satisfactory results could not be obtained in both the suppression of sedimentation and the suppression of dripping in spray coating.

[0043] [Table 3]

[0044] As shown in Table 3, the coating composition of the embodiment using deacylated gellan gum [dispersant (2-2)], a high molecular weight polysaccharide, showed a sedimentation retention rate of 98% or more even after 168 hours. In addition, in an evaluation of dripping during spray coating, almost no dripping occurred, confirming that it is possible to achieve both a high sedimentation retention rate and a good dripping suppression effect. On the other hand, the coating compositions of the comparative examples were unable to provide satisfactory results in terms of both inhibition of sedimentation and dripping during spray coating.

[0045] [Table 4]

[0046] As shown in Table 4, when polyvinyl alcohol [dispersant (2-3)], a non-carboxyl group-containing polymeric compound (non-polymeric polysaccharide), was used, the sedimentation retention rate was already below 99% after 7 hours and after 24 hours, and dripping during spray application was confirmed in most cases.

[0047] [Table 5]

[0048] [Table 6]

[0049] Furthermore, as shown in Tables 5 and 6, when a surfactant containing a carboxyl group (a low molecular weight compound, sodium polyoxyethylene lauryl ether acetate) [dispersant (2-4)] was used, it could be said that there was a certain degree of settling inhibition effect, but it did not achieve a high settling retention rate of 99% or more after 24 hours and 94% or more after 168 hours, and dripping was confirmed in all cases when spraying.

[0050] The above results demonstrate that the coating compositions of Examples 1 to 15, 16 to 29, and 30 to 38, which contain polymeric polysaccharides, are compositions in which sedimentation of the particles is suppressed compared to Comparative Example 10 to Comparative Example 24, which contain polyvinyl alcohol instead of polymeric polysaccharides, and Comparative Example 25 to Comparative Example 38, which contain a surfactant (low molecular weight compound), and that these compositions also have excellent spray applicability.

Claims

1. A coating composition comprising melamine cyanurate particles, a polymeric polysaccharide (excluding xanthan gum, azotobacter gum, scleroglucan, pullulan, and mannan), and water, The coating composition contains a polymeric polysaccharide in an amount of more than 0.05% by mass and less than 1.0% by mass based on the total mass of the coating composition. Coating composition.

2. The coating composition according to claim 1, wherein the melamine cyanurate particles have an average particle size of 0.1 to 100 μm.

3. 3. The coating composition according to claim 1, wherein the polymeric polysaccharide is a polysaccharide having a carboxylate anion in water.

4. 3. The coating composition according to claim 1, wherein the polymeric polysaccharide is a water-insoluble polysaccharide selected from the group consisting of cellulose, chitin, chitosan, and carboxylic acid modified products thereof.

5. The coating composition according to claim 1 or 2, wherein the polymeric polysaccharide is a water-soluble polysaccharide selected from the group consisting of hyaluronic acid, gellan gum, deacylated gellan gum, rhamsan gum, diutan gum, carrageenan, salts thereof, and carboxylic acid-modified products thereof.

6. 6. The coating composition according to claim 1, wherein the polymeric polysaccharide is contained in an amount of 0.1 to 0.5% by mass based on the total mass of the coating composition.

7. The coating composition according to any one of claims 1 to 6, wherein the melamine cyanurate particles are contained in an amount of 0.1 to 20% by mass based on the total mass of the coating composition. Composition.

8. A method for forming a coating film containing melamine cyanurate particles, comprising spraying the coating composition according to any one of claims 1 to 7 onto a substrate.

Citation Information

Patent Citations

  • Aqueous lubricant composition

    JP1982008297A

  • Preparation of surface-treated melamine cyanurate powder and flame-retardant resin composition containing the same

    JP1994157820A

  • Resinoid grinding wheel and manufacture thereof

    JP1995241774A

  • Water-based lubricant film treatment agent for solid

    JP2006335838A

  • Lubricant composition

    JP2008088297A